Peran Firm Size dalam Memoderasi Pengaruh Operating Capacity dan Net Profit Margin Terhadap Financial Distress - Shayla Ayuningtias; Dahlia Tri Anggraini (Jurnal Akuntansi dan Governance, 2026)
Objectives: analyzing the role of firm size in moderating the influence of operating capacity and net profit margin on financial distress in the pharmaceutical sector listed on the Indonesia Stock Exchange (IDX) during the period 2020-2024. Design/method/approach: this study used quantitative methods with secondary data collected from financial reports available on the official website of the Indonesia Stock Exchange. The number of sample was eleven (11) companies. This study uses Moderating Regression Analysis (MRA) for data analysis. Results/findings: The results indicate that operating capacity has no significant effect on financial distress, while net profit margin has a significant positive effect. In terms of moderating effect, firm size cannot moderate the effect of operating capacity on financial distress, but firm size does moderate the effect of net profit margin on financial distress. Theoretical contribution: The results confirm the validity of the signaling theory, which states that signals in financial reports can indicate positive or negative company growth. Positive financial signals indicate increasing company growth, while negative signals indicate negative growth. Therefore, this study contributes to increasing insight into the signs of financial distress in pharmaceutical companies in Indonesia. Practical contribution: The research results can be a reference for shareholders and other stakeholders in detecting financial distress that occurs in the pharmaceutical industry, as seen in signals from financial reports, especially those related to fluctuations in operating capacity, net profit margin, and firm size moderation. Limitations: The coefficient of determination value is classified as moderate, namely 52%, while the remaining 48% is explained by other variables not examined in this study